MINIMIZING THE RATE OF STUDENTS DEVIANT BEHAVIOURS THROUGH INSTRUCTION IN SOCIAL STUDIES IN EKITI AND ONDO STATES, NIGERIA (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study examines the need to reduce deviant behaviours among junior secondary schools through the teaching of Social Studies. Deviant behaviours manifest in many ways among the junior secondary school students in Nigeria. The impact of such behaviour is not only felt in the academic achievement of students but also manifests in the social vices committed by these students in the community. This study raises question about the nature of deviant behaviours manifested by these students and also raises questions about the causative factors and the influence of Social Studies instruction in minimizing the rate of deviant behaviours among the students. The population of the study is the Social Studies teachers in Ekiti and Ondo States Secondary Schools. The sample consists of One hundred and fifty teachers of Social Studies selected through random sampling technique from Ekiti and Ondo States. Two research questions and two hypotheses were formulated for the study. The Instrument for the study was a questionnaire designed for teachers. The questionnaire elicits information on the teachers perception on if Social Studies instruction could serve as a means of reducing students deviant behaviours. The data collected from the respondents were analysed using t. test statistics. It was found that teachers perceived that the deviant behaviours of the students will reduce significantly if they were taught Social Studies contents in school specifically in its areas that teach morals and culture. It was therefore recommended that the teachers should emphasise the lessons derived from the teaching of any Social Studies concepts in the secondary school.